Comparative efficacy of three antiseptics as surgical skin preparations in dogs - Boucher, Charles; Henton, Maryke M.; Becker, Piet J.; Kirberger, Robert M.; Hartman, Marthinus J. (Veterinary surgery, 2018)
Objective To compare the antimicrobial efficacy of a 2% chlorhexidine gluconate and 70% ethanol solution (CG+A) with that of F10 Skin Prep Solution (F10) and electrochemically activated water (EAW) when used as a surgical preparation in canine patients. Study design Prospective randomized clinical study. Sample population One hundred sixteen dogs presented for ovariohysterectomy. Methods Dogs were randomly divided into 1 of the 3 antiseptic groups (CG+A, F10, EAW). Skin samples with replicating organism detection and counting plates were taken at 4 different perioperative sites and time intervals (postskin preparation, postskin antisepsis, 2 hours after the second sample, and at the end of surgery) during ovariohysterectomies performed by students. The colony forming unit (CFU) counts from each sample were quantified according to the level of bacterial contamination. Zero CFU was defined as no contamination, 1‐12 CFU was defined as low contamination, and greater than 12 CFU was defined as high contamination. The 3 antiseptics were compared with respect to the level of contamination. Results There was no difference in the level of colonization between the antiseptics at the first sampling time (P = .454). However, the level of contamination for CG+A was lower compared with F10 and EAW at the second, third, and fourth sampling times (P =  .001, P =  .01, P =  .02, respectively). Conclusion CG+A was more effective at achieving a zero CFU count and low levels of contamination compared with F10 and EAW for surgical preparation in dogs undergoing ovariohysterectomy. Clinical significance This study does not provide evidence to support the use of F10 and EAW instead of CG+A for the surgical skin preparation of dogs undergoing ovariohysterectomy.